Unnatural selection : how we are changing life, gene by gene - Monosson, Emily (Island Press, 2015)
Gonorrhea. Bed bugs. Weeds. Salamanders. People. All are evolving, some surprisingly rapidly, in response to our chemical age. In Unnatural Selection, Emily Monosson shows how our drugs, pesticides, and pollution are exerting intense selection pressure on all manner of species. And we humans might not like the result. Monosson reveals that the very code of life is more fluid than once imagined. When our powerful chemicals put the pressure on to evolve or die, beneficial traits can sweep rapidly through a population. Species with explosive population growththe bugs, bacteria, and weedstend to thrive, while bigger, slower-to-reproduce creatures, like ourselves, are more likely to succumb. Unnatural Selection is eye-opening and more than a little disquieting. But it also suggests how we might lessen our impact: manage pests without creating super bugs; protect individuals from disease without inviting epidemics; and benefit from technology without threatening the health of our children.